How Do Macroeconomic Shocks Affect Banks’ Net Interest Margin? Evidence from a Dynamic Panel of Indonesian Bank - Doddy Ariefianto; Brian Steven Lim; Hans Gunadi; Sabrina Gunawan (Jurnal Akuntansi dan Bisnis, 2026)
This study investigates how macroeconomic shocks—specifically policy rate changes, exchange rate fluctuations, and real economic growth—affect banks’ Net Interest Margin (NIM) in Indonesia. Utilizing a monthly panel of 91 banks from 2012 to 2023, we estimate a Panel Vector Autoregression (PVAR) model and apply a dynamic multiplier framework to trace the temporal effect of each macro shock on NIM. The results indicate that NIM adjusts to these shocks in a time-limited and convergent manner, typically over a 6–12 month horizon. Notably, increases in the policy rate or real GDP growth are associated with a short-run decline in NIM, whereas exchange rate changes do not exert a statistically significant influence. Additional analyses across bank ownership types, size segments, and the COVID-19 period reveal considerable heterogeneity in shock transmission patterns. These findings emphasize the importance of differentiating bank-specific attributes and market contexts in understanding the pricing behavior of financial intermediation under macroeconomic stress.